Barbeque with air ventilation system - Wan Nur Amira Shafikah, Wan Mohd Fazli (2018)
Nearly half of the world’s human population used barbeque for party or gathering with family or friends. This thesis aspires to have a conventional and altenative source of the baqberque with ventilation system.The problem of the thesis was to research about the time of barbeque produce products. Identify good quality charcoal and reduce negative effect towards environment and human health. The main objective was to segment to improve the heat transfer performance of conventional charcoal because if heat directly touch to charcoal Animal testing has shown exposure to high levels of chemicals such as these is linked with cancer, Combusting wood, gas, or charcoal emits chemicals known as Polycyclic Aromatic Hydrocarbons. To design a portable charcoal barbeque set with air ventilation system. The material we use is zinc. stainless steel, blower, battery and hot rack. Designing was started by drawing a few designs using NX10 software. After run an analysis on those design and once a desired design was selected, then fabrication are started. Fabrication flow starts with a material selection were a material used was stainless steel. Then the material was cut into desired measurement. Those pieces are then welded togetger by using MIG welding machine. Machine setting parameter will be0 explained on chapter 3 methodology. The final part of this fabrication was finishing part. The structure painted so that it would be not rusted and in order to have structure with better looks.